2021
DOI: 10.2147/dddt.s255582
|View full text |Cite
|
Sign up to set email alerts
|

Translational Regulation in Hepatocellular Carcinogenesis

Abstract: The mortality of hepatocellular carcinoma (HCC) is distributed unevenly worldwide. One of the major causes is hepatitis B or hepatitis C virus infection and the development and progression of liver cirrhosis. The carcinogenesis of HCC is among others regulated via the mTOR (mechanistic target of rapamycin) signaling pathway and represents a possible method of targeted treatment. The aim of our article was to address the most recent clinical advances and findings of basic studies on the mTOR signaling pathway a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Gene expression is regulated primarily at levels of transcription and translation. Deregulation of mRNA translation, especially at the rate‐limiting step of translational initiation, results in a global increase of protein synthesis or selective enhanced translation of oncogenic mRNAs, which may play an important role in cancer development and progression (Bracic Tomazic et al., 2021 ; Robichaud et al., 2019 ; Silvera et al., 2010 ). In HCC, previous studies have reported the enhanced expression of translation factor mRNAs including both EIFs and ribosomal proteins (RPs) (Kondoh et al., 2001 ; Shuda et al., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression is regulated primarily at levels of transcription and translation. Deregulation of mRNA translation, especially at the rate‐limiting step of translational initiation, results in a global increase of protein synthesis or selective enhanced translation of oncogenic mRNAs, which may play an important role in cancer development and progression (Bracic Tomazic et al., 2021 ; Robichaud et al., 2019 ; Silvera et al., 2010 ). In HCC, previous studies have reported the enhanced expression of translation factor mRNAs including both EIFs and ribosomal proteins (RPs) (Kondoh et al., 2001 ; Shuda et al., 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, 40-50% of patients upregulate the mTORC components [115]. Similarly, many of the downstream mTOR, as well as mTOR-independent eIFs, are reported to be upregulated in HCC [116]. Obviously, these molecules are all key components, with tumor characteristic hallmarks ranging from sustained proliferation to resistance to growth repression.…”
Section: Mtor Signalingmentioning
confidence: 99%
“…It has been identified as an inhibitor of eukaryotic initiation factor 4A (eIF4A), one of the eukaryotic translation initiation factors, and is noted for its high specificity and tolerability in animal models [8]. The overactivity of translation initiation factors is closely linked to translation dysregulation, a condition that is strongly associated with excessive cell proliferation, angiogenesis, survival, and altered energetics in tumors [9,10]. Consequently, silvestrol has demonstrated the capability to inhibit the growth of numerous cancer cell lines at low nanomolar concentrations [11][12][13][14], especially targeting mRNAs with highly structured 5′UTR that are heavily reliant on eIF4A for translation [15].…”
Section: Introductionmentioning
confidence: 99%